Understanding the links between parenting and adolescents’ first sexual experience: a systematic review - Mohammad, Mohd Taufik; Vleioras, Georgios; Tan, Soon‑Aun (Springer, 2025)
Parenting practices are important regulators in an adolescent’s healthy sexual development, such as the timing of sexual debut. However, because parenting includes a vast spectrum of behaviors, it is important, for both practice and policy, to identify the ones that are related to the timing of sexual debut. In this systematic review, we made a search in Scopus with supplementary searches in EBSCOhost and in reference lists to identify articles reporting studies examining the relationship between parenting practices and the timing of sexual debut. The search process resulted in the selection of 19 studies. Most studies selected showed that while most parenting practices have significant relationships with the timing of sexual debut in bivariate analyses, multivariate analyses provided a more complex picture. The review also included family structure as the studies showed that it is an important element in parenting practices. The review demonstrates that in multivariate analyses, family structure seems to be more important in determining the timing of sexual debut, followed by parental control and monitoring. Our review has pointed that the relationship between parenting practices and the timing of sexual debut should be explored further, given the mixed findings when comparing between levels of analyses. Furthermore, in terms of professional practice, such as in the contexts of social work or psychology, focusing on family structure, parental control and monitoring could be essential in regulating the onset of sexual behavior among adolescents.